Gender Equality: Evaluation and Lithuanian Public Opinion - Juraitė, Kristina; Zdanevičius, Arnas (Sociologija. Mintis ir veiksmas, 2004)
The main goal of the article is to analyze public attitudes towards gender equality and issues of normative and empirical equality in Lithuania. Following theoretical assumptions, it is aimed at examining of what kind of attitudes people have impact towards gender equality, how sociodemographic characteristics, particularly gender, differentiate them and what kind of factors may explain these differencies. The analysis is based on the empirical data collected in the framework of the sociological research EU Enlargement and Its Commitment to Women carried out by the Department of Sociology, Vytautas Magnus University in 2004. The authors discuss different aspects of gender equality in public opinion, as well as recommendations regarding the improvement of gender policy that are interesting and valuable from the practical, as well as theoretical points of view. What kind of theoretical models and measurements can help to avoid the most frequently made mistakes when analyzing public opinion on the issues of gender equality and policy recommendations? How important is the research on the assessment of gender equality from the methodological point of view? The authors aim at answering the questions by examining the factors that foster or weaken traditional and liberal attitudes towards gender relations on individual and structural levels and shape gender policy recommendations.